Pelatihan Pemasaran Digital 6.0 Pada Sekolah SMA Buddhi Dharma Tangerang - Suhendra Suhendra; Agustinus Priyowidodo; Alexander Alexander; Limajatini Limajatini; Nana Sutisna; Rinintha Parameswari; Jayaputra Budiman (Universitas Kristen Indonesia Toraja, 2024)
The Digital Marketing 6.0 Training Program at SMA Perguruan Buddhi Dharma Tangerang was implemented to improve students' digital literacy and marketing skills in the era of digital transformation. The underlying problem of this training is the low level of students' understanding of technology-based marketing, which is an essential skill in the modern world of work and entrepreneurship. The purpose of this activity is to equip students with an understanding of the concept of digital marketing 6.0, technical skills in using digital tools, and skills in developing data-based marketing strategies. The methods used include the Community-Based Action Planning approach involving students, teachers, and community service teams, as well as experiential learning through simulations and direct practice.The results of the training showed a 40% increase in students' understanding of the concept of digital marketing as well as the ability to use digital tools and develop effective marketing strategies. In addition, this training gave rise to local leaders among students and created new awareness in the school community about the importance of technology integration in education. The collaboration between SMA Perguruan Buddhi Dharma and Universitas Buddhi Dharma also created a more inclusive and sustainable learning ecosystem. This training is expected to be a model for developing digital literacy for other schools in facing the challenges of the digital era.